UI/UX Web Based Learning Design with UCD Approach to Basic Programming using FIGMA - Etistika Yuni Wijaya; Muchamad Arif; Nuru Aini; Yiyin Noriyah Putri (bit-Tech, 2024)
The era of revolution 4.0 has had the impact of technological changes in learning, to learning in the form of technology. Online learning is designed using online technology and material is adapted to user needs. Web Based Learning is a website-based learning media that students use to learn the basics of programming. The problem of learning programming for vocational school students is that it is difficult to understand the basic syntax of programming and the flow of thinking, so learning media is needed that can make it easier for students to learn it. Interface design is one of the determinants of students' learning interest, so an appropriate design method is needed according to students' needs, namely using the UCD (User Center Design) method. So that the interface looks attractive, and the workflow is clear enough, an interface design assistant application, namely Figma, is used. Activities are emphasized on SUS testing by obtaining test results of Based on the prototype evaluation results, a MAUS score of 95 out of 100 was obtained at a high level. The MAUS value is at a high level. Meanwhile, the MIUS scores of the four scenarios tested received their respective scores, scenario 1 got a score of 76.25 with a medium level, scenario 2 got a score of 87.6 with a high level, scenario 3 got a score of 87.6 with a high level, and scenario 4 gets a score of 95.45 with a high level.